Isolated Diastolic Hypertension and Risk of Cardiovascular Disease: Controversies in Hypertension - Pro Side of the Argument. Issue 8 (14th July 2022) - Yano, Yuichiro; Kim, Hyeon Chang; Lee, Hokyou; Azahar, Nazar; Ahmed, Sabrina; Kitaoka, Kaori; Kaneko, Hidehiro; Kawai, Fujimi; Mizuno, Atsushi; Viera, Anthony J.
Abstract : Isolated diastolic hypertension (IDH), defined as diastolic blood pressure in the hypertensive range but systolic blood pressure not in the hypertensive range, is not uncommon (<20%) among adults with hypertension. IDH often manifests in concurrence with other cardiovascular risk factors. Individuals with IDH tend to have lower awareness of their hypertension compared with those with both systolic and diastolic hypertension. IDH appears to be a largely underrated risk factor for cardiovascular disease events, which may be explained by inconsistent association of IDH with cardiovascular disease events. The inconsistency suggests that IDH is heterogeneous. One size does not seem to fit all in the clinical management of individuals with IDH. Rather than treating IDH as a monolithic low-risk condition, detailed phenotyping in the context of individual comprehensive cardiovascular risk would seem to be most useful to assess an individual's expected net benefit from therapy. In this review, we highlight that the clinical relevance of IDH differs by individual clinical characteristics, and elucidate groups of individuals with IDH that should be wary of cardiovascular disease risks.